Percutaneous catheter drainage of secondary abdominal compartment syndrome: A case report - Patel, Aditi (Radiol Case Rep, 2021)
Abdominal compartment syndrome can be a lethal entity when not treated in a timely fashion. Current standard of care involves emergent decompressive laparotomy by the surgical team. In this case, a 52-year-old male who developed abdominal compartment syndrome secondary to hemoperitoneum underwent emergent drain placement as decompressive laparotomy was not an optimal option for management. Little literature exists on the utility of drain placement or paracentesis for decompression in overall patient morbidity and mortality. However, when necessary, drain placement shows similar outcomes when compared to the standard of care. Interventional radiologists are uniquely positioned to provide drainage guided management for abdominal compartment syndrome in emergent settings.